Effectiveness of Implementing DIR/Floortime Principles to Improve Expressive Language of 2-years-old Child with Language Delay: A Coaching Approach for Mother - Nursyifa Az Zahra; Lia M. Boediman (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to review the effectiveness of coaching approaches for mothers by implementing the DIR/Floortime principles to improve expressive language in a 2-year-old child with language delay. This intervention consists of three components: 1) Developmental (D); 2) Individual Difference (I); 3) Relationship Based (R). The research design is Small-N Design in a single case with one participant: the boy with a language delay and his mother. The measurement methods used were observation and interview based on the Functional Emotional Assessment Scale (FEAS), Circle of Communication (CoC) form, and a logbook for recording spoken new vocabulary. This research indicated that implementing DIR/Floortime principles effectively improves expressive language in a 2-year-old child with language delay.